Reflexão sobre o ensino de canto para alunos de um curso de licenciatura em teatro - Mangini, Maurício Machado [UNESP] (My University, 2013)
The aim of this study was to reflect on the purpose of teaching singing to future teacher teachers. A literature survey has been processed, oriented by the author's experience, a music professor, to propose a discussion of relevant aspects that regard the use of the singing voice by the actor who also works as an art educator. Among the results of the study, the highlight was the use of the teaching of singing as a music education tool for theatre students. The article concludes that teaching singing in the portrayed context is an active process for development of musical expression through voice and speech.
Reflection on teaching singing for students of a degree course in theater
Keywords: Interdisciplinary practices in arts; Music education through voice; Teaching singing for actors